Glucagon-like peptides-1 from phylogenetically ancient fish show potent anti-diabetic activities by acting as dual GLP1R and GCGR agonists. (15th January 2019) - Graham, Galyna V.; Conlon, J. Michael; Abdel-Wahab, Yasser H.; Flatt, Peter R.
Abstract: Glucagon-like peptides-1 (GLP-1)from phylogenetically ancient fish (lamprey, dogfish, ratfish, paddlefish and bowfin) and from a teleost, the rainbow trout produced concentration-dependent stimulations of insulin release from clonal β-cells and isolated mouse islets. Lamprey and paddlefish GLP-1 were the most potent and effective. Incubation of BRIN-BD11 cells with GLP-1 receptor (GLP1R) antagonist, exendin-4 (9–39) attenuated insulinotropic activity of all peptides whereas glucagon receptor (GCGR) antagonist [des-His 1, Pro 4, Glu 9 ] glucagon amide significantly decreased the activities of lamprey and paddlefish GLP-1 only . The GIP receptor antagonist GIP (6–30) Cex-K 40 [Pal] attenuated the activity of bowfin GLP-1. All peptides (1 μM) produced significant increases in cAMP concentration in CHL cells transfected with GLP1R but only lamprey and paddlefish GLP-1 stimulated cAMP production in HEK293 cells transfected with GCGR. Intraperitoneal administration of lamprey and paddlefish GLP-1 (25 nmol/kg body weight) in mice produced significant decreases in blood glucose and increased insulin concentrations comparable to the effects of human GLP-1. Lamprey and paddlefish GLP-1 display potent insulinotropic activity in vitro and glucose-lowering activity in vivo that is mediated through GLP1R and GCGR so that these peptides may constitute templates for design of new antidiabetic drugs. Highlights: Lamprey, dogfish, ratfish, paddlefish, bowfin and trout GLP-1 stimulated insulin release from clonal β-cells and islets. Insulinotropic activity of lamprey and paddlefish GLP-1 was attenuated by a GCGR antagonist. All peptides stimulated cAMP production in CHL cells transfected with GLP1R. Lamprey and paddlefish GLP-1 stimulated cAMP production in HEK293 cells transfected with GCGR. All peptides improved glucose tolerance in mice with lamprey and paddlefish GLP-1 as effective as human GLP-1.